A Multicentric, Retrospective Efficacy and Safety Study of Nanosomal Docetaxel Lipid Suspension in Metastatic Castration-Resistant Prostate Cancer. (16th December 2020) - Samar, Aseem; Tiwari, Srikant; Subramanian, Sundaram; Joshi, Nisarg; Sejpal, Jaykumar; Khan, Mujtaba A.; Ahmad, Imran
Abstract : Purpose . To evaluate the efficacy and safety of nanosomal docetaxel lipid suspension (NDLS, DoceAqualip) in patients with metastatic castration-resistant prostate cancer (mCRPC). Materials and Methods . In this multicenter, retrospective study, we analyzed the medical charts of mCRPC patients, who were treated with NDLS administered as 2-weekly (50 mg/m 2 ) or 3-weekly regimens (75 mg/m 2 ). The study endpoints were prostate-specific antigen (PSA) response (>50% PSA decline from baseline), PSA progression (PSA increase from baseline beyond 12 weeks: ≥25% and ≥2 ng/mL), median PSA decline, and time-to-treatment failure (TTF). Overall survival (OS) and safety were also evaluated. Results . Data of 24 patients with mCRPC were analyzed in this study. NDLS was administered as a 2-weekly regimen in 37.5% (9/24; all first-line) patients and as a 3-weekly regimen in 62.5% patients (15/24; first-line: 20% (3/15), second-line: 80% (12/15)). Overall, PSA response was reported in 66.7% (16/24) patients. The PSA response was 77.8% (7/9 patients) in the 2-weekly group and 60% (9/15 patients) in the 3-weekly group. The median decline in PSA was 96.31% in the 2-weekly group and 83.29% in the 3-weekly group; the median TTF was 6.7 and 6.5 months in the 2 weekly group and 3-weekly group, respectively. The median OS was 14.6 months (follow-up: 5.5–25.8 months) in the 2-weekly group whereas it was not reached in the 3-weekly group (follow-up: 7.9–15.6 months). The most common hematological AEs were anemia, lymphopenia, thrombocytopenia, and neutropenia whereas nausea, weakness, constipation, vomiting, and diarrhea were the most common (≥10%) nonhematological AEs. Overall, NDLS treatment was well tolerated without any new safety concerns. Conclusions . Nanosomal docetaxel lipid suspension (2-weekly or 3-weekly) was effective and well tolerated in patients with metastatic castration-resistant prostate cancer.